Who Needs Bands? : Exchange Rate Policy Before Emu - Bayoumi, Tamim (Washington, D.C. : International Monetary Fund, 1995)
Two issues are discussed. The first is which countries might benefit from entry into EMU before the millennium. Germany and her immediate neighbors appear the most likely to gain; however, our knowledge is too uncertain to say whether all, some, or no countries would reap net economic benefits. The second issue is how to avoid exchange rate instability in the transition to EMU. Experience from earlier exchange rate regimes suggests that an early announcement the parities at which different currencies would enter EMU could reduce such instability if governments were willing to accept the required limitations on domestic policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet